AB0124 Peripheral Blood Mononuclear Cells from Ankylosing Spondylitis Patients Display An Atherogenic Profile Associated with Disease Activity and Endothelial Dysfunction. (15th July 2016) - Jimenez-Gomez, Y.; Font, P.; Pérez-Sánchez, C.; Ruiz-Limόn, P.; Barbarroja, N.; Άbalos-Aguilera, M.C.; Castro-Villegas, M.C.; Ortega-Castro, R.; Calvo, J.; Lόpez-Pedrera, C.; Escudero-Contreras, A.; Collantes-Estévez, E.
Abstract : Background: Several studies have demonstrated that Ankylosing Spondylitis (AS), a chronic inflammatory disease of unknown aetiology, is associated with several comorbidities such as cardiac pathology, accelerated atherosclerosis and cardiovascular disease. Yet, the relevance of peripheral blood mononuclear cells (PBMCs) in the development of atherosclerosis in AS patients is not fully known. Objectives: 1) To analyze the gene expression profile associated with the development of atherosclerosis in PBMCs from AS patients. 2) To evaluate the role of PBMCs in the endothelial dysfunction present in AS patients. Methods: Twenty five patients with AS and 25 healthy donors were included in the study. Disease function and activity status were analyzed using the BASFI and BASDAI indexes, respectively. The expression of 84 genes related to atherosclerosis was analyzed in purified PBMCs by PCR array, using total ARN pools of patients and healthy donors. Next, validation of several differentially expressed genes in PBMCs, selected on the basis of their expression levels and relevance in AS pathology, was carried out in our patient and healthy donor cohort. Endothelial function was determined by the post occlusive hyperaemia test using Laser-Doppler. To analyze the role of PBMCs in endothelial function, in vitro co-cultures of endothelial cells (HUVEC) and PBMCS from AS patients with different inflammatory status were performed. Results: The endothelial function analysis demonstrated a significant reduction of post occlusive hyperaemia area in AS patients in relation to healthy donors, thus pointing at the presence of a prominent endothelial dysfunction in these patients. The analysis of the genetic profile in PBMCs showed a significant alteration in the expression of genes related to inflammatory (CCL2, CCL5, CCR1, CCR2, IL1R2, IL1A, IL2, IL5, NOS3, SPP1), and oxidative stress response (APOE, SOD1). An altered expression of genes linked to cellular adhesion (CDH5, ICAM-1, SELL, SPP1, CTGF, FN1, THBS4, TNC), lipid metabolism and transport (ABCA1, APOA1, APOE, FABP3, LPL, LPA, MSR1), cell growth and proliferation (CSF2, SSP1, BCL2, FABP3, FGF2, LIF, CRGF), as well as transcription and apoptosis regulators (PPARA, PPARD, EGR1, BCL2, BCL2A1, BCL2L1) was further demonstrated. In vitro treatment of HUVECs with PBMCs from AS patients with a high pro-inflammatory profile promoted a significant activation of the endothelial cells, which displayed increased expression of adhesion molecules, oxidative stress markers, cytokines and chemokines, all of them associated to the pro-atherogenic profile of these patients. Conclusions: 1) Peripheral blood mononuclear cells from AS patients display an altered expression profile of key genes involved in the development of atherosclerosis. 2) That highly inflammatory PBMCs are responsible, at least partially, for the endothelial dysfunction displayed by AS patients. Acknowledgement: Funded by JA PI-0314–2012, SER Disclosure of Interest: None declared